Glosa aprobująca do wyroku Trybunału Konstytucyjnego z dnia 16 listopada 2011 roku, Sygn. akt SK 45/091 - Etynkowska, Eliza (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
In the commentary, the author expresses his general approval of the judgment of the Polish Constitutional Tribunal 16 Nov 2011. This article examines the acceptability of controlling secondary law of the European Union by lodging a constitutional complaint to the Constitutional Tribunal. It presents the nature of a constitutional complaint, the relationship between domestic law and EU law as well as examples of judgments from other European countries.
Keywords: glosa; Trybunał Konstytucyjny - sygn. akt SK 45/091